The application and concept of the theory of five colour in ancient Chinese urban architecture / YaoDong Ma and Alamah Misni - YaoDong, Ma; Misni, Alamah (Faculty of Art and Design, 2024)
This study explores the application and concept of the Theory of Five colours in ancient Chinese urban architectural design. Nowadays, urban colour has emerged as a crucial aspect of urban planning, carrying significant historical, cultural, and aesthetic information in the evolution of cities. Colour plays a symbolic role in expressing the character and quality of cities, with its impact evident in various aspects of human habitation and daily life. The conceptual analysis via on-site observation and secondary data delves into the historical shifts in architectural colour schemes for various periods, including the Warring States, the Qin Dynasty, the Han Dynasty, the Wei-Jin Northern and Southern Dynasties, and the Tang, Song, Ming, and Qing Dynasties. Through an analysis of the evolution of architectural colour across different historical eras, the finding reveals that the use of colour in ancient Chinese urban architecture was rooted in the traditional Theory of Five colours. Notably, red and yellow predominantly adorned noble, imperial, and religious structures, underscoring their esteemed and sacred significance. Conversely, colours like black, white, and green were prevalent in civilian constructions, emphasising the vibrancy and diversity of primary buildings through extensive use of neutral colours. This practice of colour differentiation contributed to distinctive regional variations within cities, reflecting a hierarchical architectural concept. However, with the passage of time and the disappearance of the hierarchical system, the application of colour in urban architecture became more flexible. Modern urban architecture, based on the foundation of ancient urban colour, exhibits diverse expressions according to factors such as cultural history, geographical location, and urban characteristics. As a result, the architectural landscapes of different cities display rich and varied colour palettes. These research findings will contribute as a significant reference value for the cultural connotations of ancient urban architecture and the colour design of modern urban spaces in China.